Economic and Policy Determinants of Indonesia’s Rice Imports: an Empirical Assessment - Septya, Fanny; Aglobosoo, John Atsu; Novianti, Tanti; Nurfitasari, Mimi (Jurnal AGRISEP, 2026)
This study examined the factors affecting Indonesia's rice imports between 1990 and 2024. Despite efforts to become self-sufficient in rice, Indonesia remains dependent on imports because of price differences, population growth, and fluctuating domestic production. To investigate both short-term and long-term relationships among important variables, such as domestic rice production, exchange rate, national income, domestic rice prices, population, and import tariffs, this study used secondary time series data and the autoregressive distributed lag (ARDL) model in conjunction with the error correction model (ECM). The findings demonstrate that exchange rate depreciation has a substantial impact on rice imports, raising import costs without significantly lowering volumes because of the inelastic nature of rice demand. Higher import volumes are positively correlated with population growth and domestic price increases. Tariffs are found to have delayed effects in later periods but have a statistically negligible impact in the short term. The interdependence in the macroeconomic environment is indicated by the confirmed long-term equilibrium relationships between the variables. Based on the ARDL results, the error correction term (ECT) coefficient is negative and significant for cointegration validity, reflecting how quickly rice import levels revert to their long-run relationship with the specified factors. According to the study's findings, import regulations need to reform.